Senario Fatwa-Fatwa Zakat Di Malaysia: Perspektif Maqasid Syariah - Bhari, Azri; Abdullah, Luqman (Jurnal Fiqh, 2016)
The nature of Islamic legal practice in Malaysia is known for its adherence to the views of the Shafii school in fiqh issues based on the historical background of the arrival of Islam in Malaysia and the Islamic legal practice that have been adapted. Fatwas issued by the fatwa institution in Malaysia have evolved from time to time in accordance to the principles of Islamic law, which are flexible and accommodating to the changing environment. In recent years, developments in Islamic legal practice shows the ultimate determination of fatwas especially on zakat are no longer bound to the Shafii school. This shows an openness in considering the views of other mazhab/schools and the opinions of contemporary fiqh scholars in issuing laws or fatwas relating to zakat. This can be seen in the shift from the Shafii school to the views of other schoools and the opinion of contemporary fiqh scholars on fatwas. This article determines 26 out of 191 fatwas on zakat that have been classified into six themes have shifted from the Syafii school to others. The study also reviews the principles of maqasid sharia that hasve been deliberated in determining the fatwa on zakat. This qualitative study is conducted through library research and interviews. The data collected are analysed using inductive, deductive and comparative methods. The study shows a number of fatwas on zakat that have shifted from the Syafii school. Thus, it can be concluded that the Muftis and fatwa committees in Malaysia have strived to achieve the maqasid sharia from the maslahah and mafsadah perspectives in determining fatwas on zakat.